Probing the Nano-Assembly Leading to Periodic Gratings in Poly(p-dioxanone) - Min-Han Hao; Selvaraj Nagarajan; Eamor M. Woo (Nanomaterials, 2023)
This study used scanning electron microscopy via 3D dissection coupled with synchrotron radiation with microfocal beams of both small-angle X-ray scattering and wide-angle X-ray diffraction to analyze the periodic crystal aggregates of unusual poly(p-dioxanone) (PPDO) dendritic cactus-arm-like ring bands upon crystallization with a diluent poly(vinyl alcohol) (PVA) that is capable of hydrogen bonding interactions with PPDO. Three-dimensional microscopy interior dissection clearly expounds that the banded periodic architectures are packed by alternately normal-oriented flat-on crystals underneath the valley, periodically interfaced/branched with horizontal-oriented edge-on fibrils underneath the ridge. The oblique angles between the valley’s flat-on crystals with the branches are ca. 25–45° (depending on gradient inclines and bending), which is also proved by the azimuthal angle in microbeam X-ray diffraction. The grating-like strut-rib assembly in the PPDO cactus-arm-like ring bands is further proved by novel iridescence tests.